Idiosyncratic risks, bailout, and financial crisis: A copula approach - Wang, Daphne; Nguyen, Khoa Huu (Global Business & Finance Review (GBFR), 2015)
EconStor is a publication server for scholarly economic literature, provided as a non-commercial public service by the ZBW.
Publisher: Seoul: People & Global Business Association (P&GBA)

Institutional ownership and the spillover effects of shareholder activism - Jory, Surendranath; Ngo, Thanh; Nguyen, Khoa Huu (International Journal of Corporate Governance, 2017)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-553-764-759-222, pop00160 tex.type: [object Object]
Keywords: dept.fin

Dynamic responses and tail-dependence among commodities, the US real interest rate and the dollar - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (Empirical Economics, 2017)
5 citations (Crossref) [2023-10-31]
Keywords: dept.fin